2018
DOI: 10.12659/msm.908831
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Caspofungin in Unclassified Invasive Fungal Infection Cases: A Retrospective Analysis of Patients with Hematological Malignancies in China

Abstract: BackgroundThe management of invasive fungal infection (IFI) is challenging in immunocompromised patients who do not fully satisfy the EORTC/MSG diagnostic criteria of proven or probable IFI. Our study assessed caspofungin efficacy in 582 Chinese patients with hematological malignancies exhibiting unclassified signs or symptoms of IFI.Material/MethodsThis retrospective study included caspofungin treatment outcomes of an unclassified group A (n=401) of patients without microbiological or biomarker results and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In terms of efficacy, the overall effective rate (63%) when treating with caspofungin in patients with different Child–Pugh classifications was almost consistent with the effective rate (65%) reported by Xiaohui Zhang et al [ 12 ]. There was no difference in the efficacy of caspofungin in patients with different hepatic function grades, suggesting that even without dose reduction, grade B and C patients tolerated caspofungin not differently from grade A patients and had better treatment outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of efficacy, the overall effective rate (63%) when treating with caspofungin in patients with different Child–Pugh classifications was almost consistent with the effective rate (65%) reported by Xiaohui Zhang et al [ 12 ]. There was no difference in the efficacy of caspofungin in patients with different hepatic function grades, suggesting that even without dose reduction, grade B and C patients tolerated caspofungin not differently from grade A patients and had better treatment outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that clinicians should monitor the tacrolimus concentration and should adjust the dose of immunosuppressive drugs in a timely manner if the patient requires the use of azole antifungal drugs.In both case reports in this article, antifungal treatment with caspofungin was used.Caspofungin was effective for treating unclassified invasive fungal infection of immunocompromised patients. 40 This may explain why both patients were treated with caspofungin.In a study by Jing Zhang, it can be found that, compared with amphotericin B, itraconazole, and voriconazole, caspofungin showed relatively higher MICs (minimum inhibitory concentrations) among mold and yeast forms. 41 This suggests that caspofungin is less effective in patients with TM infection.…”
Section: Discussionmentioning
confidence: 99%